Proceedings of the 5th Annual International Conference on Accounting Research (AICAR 2018) 2019
DOI: 10.2991/aicar-18.2019.34
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corporate Governance on Company’s Performance with Sustainability Reporting as an Intervening Variable in Indonesia

Abstract: This study aims to examine the effect of corporate governance on the company's performance with sustainability reporting as an intervening variable in Indonesia. The population of this study is a manufacturing company listed on the Indonesian Stock Exchange for the period 2010-2015. The sample selection used purposive sampling method and resulted in 102 manufacturing firms listed on the Indonesia Stock Exchange. The results show that: (1) Corporate governance with audit committee as a proxy affects sustainabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Again, the focus is on generating enough profits which would ensure a better reward for the owners. This result conforms with the outcome of the study in Indonesia by Machdar (2019) who found that corporate social responsibility (CSR) does not mediate the relationship between CG and organisational financial performance.…”
Section: Discussionsupporting
confidence: 91%
“…Again, the focus is on generating enough profits which would ensure a better reward for the owners. This result conforms with the outcome of the study in Indonesia by Machdar (2019) who found that corporate social responsibility (CSR) does not mediate the relationship between CG and organisational financial performance.…”
Section: Discussionsupporting
confidence: 91%
“…The company's goal is not solely oriented to intensifying the value of the owner but also to other people who are interested in the company. Stakeholder theory is one of the fundamental theories used to underlie research on sustainability reports (Machdar, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machdar [32] argued the concept of Profitability could be termed as the ability to make a profit from all the business activities of an organization, company, firm, or an enterprise. It reveals how efficiently the management can make a profit by using all the resources available in the market.…”
Section: Profitabilitymentioning
confidence: 99%
“…Fakir, Islam and Miah [18]; Machdar [32]; Rani and Rani [49]; Pajrok [46] studies on responsibility accounting have been inconclusive and controversial and no consensus has been reached, especially the impact of responsibility accounting on profitability. While some authors have established positive relationships in their studies, others have established negative or no relationship using shareholders' wealth as a proxy for responsibility accounting and while liquidity, return on investment; earnings per share and assets replacement were used as a proxy for profitability.…”
Section: Justification For the Studymentioning
confidence: 99%